2016
DOI: 10.1186/s13613-016-0108-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endostatin may improve acute kidney injury risk prediction in critically ill patients

Abstract: BackgroundBreakdown of renal endothelial, tubular and glomerular matrix collagen plays a major role in acute kidney injury (AKI) development. Such collagen breakdown releases endostatin into the circulation. The aim of this study was to compare the AKI predictive value of plasma endostatin with two previously suggested biomarkers of AKI, cystatin C and neutrophil gelatinase-associated lipocalin (NGAL).MethodsWe studied 93 patients without kidney disease who had a first plasma sample obtained within 48 h of ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Thirty studies161718192021222324252627282930313233343536373839404142434445 finally met the inclusion criteria via full-text evaluation from 156 potentially eligible citations. Seven studies21222324252627 were selected from the previous meta-analysis (Zhang, et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty studies161718192021222324252627282930313233343536373839404142434445 finally met the inclusion criteria via full-text evaluation from 156 potentially eligible citations. Seven studies21222324252627 were selected from the previous meta-analysis (Zhang, et al .…”
Section: Resultsmentioning
confidence: 99%
“…GaygIsIz et al 19. and Martensson et al 20. found that the predict values (AUROC) of Scys was 0.67, with low sensitivity and specificity.…”
mentioning
confidence: 99%
“…However, with accumulating evidence, conflicting results have raised. Gaygısız et al [27] and Martensson et al [28] found that the predictive value (AUC) of sCyC was 0.67, with low sensitivity and specificity. In the present study, we found that a 30% increase in sCyC was highly accurate in diagnosing CSA-AKI, with AUC 0.843 (75% sensitivity and 80% specificity).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple other functions of endostatin have been discovered beyond its anti-angiogenic properties. For example, it can modulate androgen receptor function (Lee et al, 2015) and prevent sepsis or acute kidney injury (Peng et al, 2015;Mårtensson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%